Sistem Pendukung Keputusan Penentuan Desa Terbaik Dalam Pengelolaan Dana Desa Pada Kecamatan Merdeka Kabupaten Karo Menggunakan Simple Additive Weighting (SAW) - Hori Niyoga Gurusinga; R Mahdalena Simanjorang (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2020)
In making a decision, a system that can recommend the best village is based on criteria determined by the user. Support System for Deciding the Best Village Determination in Village Fund Management in Merdeka District, Karo District using the SAW (Simple Additive Weighting) Method. The SAW method can help in making a case decision, but calculations using the SAW method only produce the greatest value that will be selected as the best alternative. Results C01, C02, C03, C04, C05, C06, C07, form the decision matrix. Normalization calculation results to get a normalized value matrix (R). Analysis Results, displays alternative data values and criteria data values. Obtained total assessment, followed by ranking. For the report, the highest total score is the result of the Best Village Assessment in managing village funds. Assessment decisions are displayed in the Report Menu.